2018
DOI: 10.1080/09637486.2017.1417977
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fermented milk containing Lactococcus lactis subsp. cremoris FC on defaecation in healthy young Japanese women: a double-blind, placebo-controlled study

Abstract: The objective of this double-blind, placebo-controlled study was to elucidate the effects of fermented milk containing Lactococcus lactis subsp. cremoris FC (FC) on defaecation in healthy young women. We included 31 women (18-31 years old) who were randomly selected into two groups. Subjects in the test group consumed fermented milk containing FC, while subjects in the placebo group consumed non-fermented gelled milk. In the test group, defaecation frequency (both in days and times per week) and stool volume s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Daily consumption of kefir also improved bowel satisfaction scores and accelerated colonic transit (Turan et al, 2014). Ozaki et al (2018) found that the fermented milk containing Lactococcus lactis ssp. cremoris FC is beneficial for improving defecation and fecal properties (Ozaki et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Daily consumption of kefir also improved bowel satisfaction scores and accelerated colonic transit (Turan et al, 2014). Ozaki et al (2018) found that the fermented milk containing Lactococcus lactis ssp. cremoris FC is beneficial for improving defecation and fecal properties (Ozaki et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Ozaki et al (2018) found that the fermented milk containing Lactococcus lactis ssp. cremoris FC is beneficial for improving defecation and fecal properties (Ozaki et al, 2018). The numbers of various beneficial fecal bacteria increased in older individuals (>60 yr old) with regular use of fermented milk containing Lactobacillus casei strain Shirota (Aoyagi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the intake of test capsules tended to increase the proportion of soft stool and reduced that of hard stool, although there were no significant differences compared with the placebo intake period. We previously described that fermented milk containing 2 × 10 10 -2 × 10 11 cfu L. cremoris FC significantly improved stool appearance [4,5]. Therefore, differences in the dose or form of the test food could explain the lack of a significant effect obtained in the study, and thus further studies are needed to explore the reasons.…”
mentioning
confidence: 95%
“…Fermented milk made with L. cremoris FC has a viscous texture due to the production of exopolysaccharide as a metabolite. We previously reported the probiotic effects of fermented milk made with L. cremoris FC on defecation and intestinal microflora in healthy adults based on a double-blind placebo-controlled study [4,5], and we detected L. cremoris FC in the feces of subjects up to 2 weeks after administration, suggesting that the bacteria can reach the intestines in a viable form [6]. Moreover, we previously reported that hard capsules containing L. cremoris FC affected defecation and intestinal microflora in healthy adults based on a double-blind placebo-controlled study [7].…”
mentioning
confidence: 99%
“…We have reported various beneficial effects of L. lactis subsp. cremoris strain FC (FC) on colitis (9), immunomodulation (10), biopreservation, antimicrobial activities (11), dermatitis (12), and healthy defecation (13). Furthermore, other groups reported the benefits of L. lactis for folate supplementation (14) and its inhibitory effects on food allergies (15), pollinosis (16), tumors (17), serum cholesterol (18), and hypertension (19).…”
Section: Introductionmentioning
confidence: 99%